HUBUNGAN PARITAS DAN DUKUNGAN SUAMI DENGAN ANEMIA PADA IBU HAMIL TRIMESTER III DI PMB HJ. MURTINAWITA, SST PEKANBARU - Rini Hariani Ratih; Nurmaliza Nurmaliza; Yusmaharani Yusmaharani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Anemia is a condition where the level of hemoglobin (Hb) in the body is below normal according to certain groups of people. Anemia in pregnancy can have a negative impact on the mother and the fetus. The adverse impact that can occur on pregnant women is that the delivery process takes quite a long time and can result in bleeding, shock due to contractions, while the adverse impact on the fetus is premature, LBW, defects and can even cause infant death. The problem of anemia in pregnancy experienced by the world was 38.2% in 2011. About half of the incidence of anemia is caused by iron deficiency. In this study, researchers used a type of quantitative research using correlation analysis, which aims to determine factors related to anemia in third trimester pregnant women at PMB Hj. Murtinawit, SST. Pekanbaru Pekanbaru in 2021. The population of this study were all pregnant women with PMB Hj. Murtinawita, as many as 104 third trimester pregnant women with anemia. The sampling technique used consecutive sampling, namely all subjects who came sequentially and met the selection criteria were included in the study until the required number of subjects was met. Which consisted of 51 samples in this study. using the Chi Square test and the basis of decision making is by comparing the value of p value with a value of 0.1, Based on the results of the study, there was a relationship between parity and the incidence of anemia in pregnant women in the third trimester P-value = 0.000, ɑ 0.1 and there was a relationship between husband's support and the incidence of anemia in pregnant women in the third trimester P-value = 0.003, ɑ 0.1. It is expected that health workers at the puskesmas can provide counseling about pregnancy to pregnant women regarding the risk of anemia in pregnancy and carry out early detection to prevent anemiaKeywords: Parity , Husband Support , Third Trimester Pregnant Women, Anemia